THU0178 Rates of Serious Infections and Malignancies among Rheumatoid Arthritis Patients Receiving Either Tnf-Blocker or Rituximab Therapy in Finland. (10th June 2014) - Aaltonen, K.J.; Joensuu, J.T.; Liisa, V.; Sokka, T.; Relas, H.; Valleala, H.; Rantalaiho, V.; Pirilä, L.; Puolakka, K.; Uusitalo, T.; Blom, M.; Konttinen, Y.T.; et al.
Abstract : Background: While randomized clinical trials have not showed an increased risk for serious infections among TNF-blocker users in comparison to methotrexate, we sought to confirm the results in Finnish routine care [1]. Objectives: The objective of the study was to investigate the incidence of serious infections and malignancies among patients with rheumatoid arthritis (RA) using either TNF-blockers, rituximab or conventional disease modifying anti-rheumatic drugs (cDMARD). Methods: Study protocol restricted inclusion to the current users of infliximab, etanercept, adalimumab or rituximab. Additionally, biologic-naïve cDMARD users were recruited as a control group. Furthermore, treatments prior to the first recorded out-patient specialized care visit were excluded from the analyses. The follow-up time included a six month lag-time to capture adverse events that occur after discontinuation but may have been due to the exposure. The study population was identified from the National Register of biological treatment in Finland (ROB-FIN) and from the hospital records of Jyväskylä Central Hospital, the latter providing all the cDMARD patients. Records on serious infections and malignancies were retrieved from the National Hospital Discharge Register and the National Cancer Register, respectively. Data from different registers were merged on the patient level using unique social security numbers. The results are presented as counts, incidence rates per 1000 patient-years (IR) and adjusted hazard ratios (HR) along with their respective 95% confidence intervals. The confounding factors included in the model comprised age, sex, disease activity, time from diagnosis, use of cortisone as well as prior infections and malignancies. Results: The study comprised 3, 542 patients accumulating 11, 337 patient years, including switchers. Between 1999 and 2011 there were 100 (IR 31, 25-38), 179 (IR 24, 21-28; HR 0.9, 0.6-1.3) and 26 (IR 35, 23-51; HR 0.8, 0.4-1.5) serious infections in the DMARD, TNF-blocker and rituximab groups, respectively. The most common serious infections included erysipelas, sepsis, gastroenteritis, bronchitis along with tuberculosis. The results for new-onset malignancies among cDMARD, TNF-blocker and rituximab groups were 39 (IR 12, 9-17), 45 (IR 6, 4-8; HR 1.2, 0.67-2.4) and 7 (IR 9, 4-19; HR 0.7, 0.2-3.0), respectively. Conclusions: Nor the unadjusted or adjusted results found evidence of increased risk for serious infections or malignancies among TNF-blocker or rituximab users compared to the cDMARD users. References: Aaltonen KJ, Virkki LM, Malmivaara A, et al. Systematic Review and Meta-Analysis of the Efficacy and Safety of Existing TNF Blocking Agents in Treatment of Rheumatoid Arthritis. PLoS One 2012;7:e30275. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2568